Studies on the Macrocycle Mediated Transport in a Bulk Liquid Membrane System of Transition Metal Cations - Hossein Rounaghi, Gholam; Ghaemi, Arezoo; Chamsaz, Mahmood (Asian Journal of Chemistry, 2011)
A series of competitive metal ion transport experiments have been performed. Each involved transport from an aqueous source phase across an organic membrane phase into an aqueous receiving phase. The source phase consisted of a buffer solution (CH3COOH/CH3COONa) at pH = 5 and containing an equimolar mixture of Co2+, Fe3+, Cd2+, Cu2+, Zn2+, Ag+ and Pb2+ metal cations. The organic phase contained the macrocyclic ligand, 1,10-dodecyl-1,10-diaza-18-crown- 6 (Kryptofix 22DD) as an ionophore and the receiving phase consisted of a buffer solution (HCOOH/HCOONa) at pH = 3. The results show that the ionophore is selective for silver cation. The effects of various organic solvents on cation transport rates have been demonstrated. Among the organic solvents involving nitrobenzene (NB), chloroform (CHCl3), dichloromethane (DCM), 1,2-dichloroethane (1,2-DCE), chloroform-nitrobenzene (CHCl3-NB) and chloroformdichloromethane (CHCl3-DCM) binary systems which were used as liquid membrane, a good transport efficiency and selectivity was obtained for Ag+ cation. The sequence of transport rate for Ag+ cation in the pure organic solvents was found to be: DCM > CHCl3 > NB > 1,2-DCE. The non-linear behaviour was observed for variations of the transport rate of silver cation versus the composition of chloroform-nitrobenzene and chloroform-dichloromethane binary mixtures was discussed in terms of changing the chemical and physical properties of the constituents solvents when they mix with one another. The influence of fatty acids as surfactant in the membrane phase on the transport of metal cations was also investigated.